Successful Management of Pulmonary Arterial Hypertension by Monitoring N-Terminal Pro-B-Type Natriuretic Peptide Serum Levels in a Preterm Infant with Chronic Lung Disease: A Case Report - Keigo Seki; Satoru Iwashima; Hiroki Uchiyama; Akira Ohishi; Takamichi Ishikawa (Thieme Medical Publishers, Inc., 2019)
We measured the serial changes in N-terminal probrain natriuretic peptide (NT-proBNP) levels in a 6-month-old male infant with chronic lung disease (CLD) complicated by pulmonary arterial hypertension (PAH). The patient was born at the 24th week of gestation weighing 695 g. At 1 month after birth, an echocardiogram confirmed the diagnosis of CLD with PAH. He was treated with inhaled nitric oxide (iNO) and oral sildenafil and discharged from the hospital. At 190 days of age, the patient was readmitted to our department because of a viral upper respiratory infection. At 195 days of age, his respiratory condition worsened with pulmonary edema and his NT-proBNP level was determined to be 10,117 pg/mL. The patient was immediately administered iNO, and his respiratory condition improved, and NT-proBNP levels decreased. However, he experienced repeated severe cyanosis attacks. Before the attacks, his NT-proBNP level was > 1,000 pg/mL. Therefore, we continuously administered iNO until his NT-proBNP level decreased to < 1,000 pg/mL. We safely discontinued iNO administration at 473 days of age. In conclusion, serial change in NT-proBNP is a surrogate marker with prognostic value in patients with PAH associated with CLD.